Youth of Today, Teenagers of Yesterday in Uruguay: Maternity and Performances - Varela Petito, Carmen; Lara, Cecilia (Sociedad y Economía, 2015)
This paper studies the social performance of two cohorts of Uruguayan young women, which completed the last youth stage in 1990 and 2008. It compares between teenage mothers and those that were not. The differences among both groups are analyzed considering the gaps in: parity achieved, education, labor market, poverty and home confinement. Besides, the interrelationship of the first birth event with other events related to the transition to adulthood is inquired. The theoretical-methodological approach is based on the course of a lifetime. The main results reveal that the teenage mothers arrive to adulthood with scarcities which limit their social inclusion.